2022
DOI: 10.3390/ma15020539
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Kinetics of Bainite Transformation Behaviour in a High-Silicon Medium-Carbon Steel above and below the Ms Temperature

Abstract: This work deals with the kinetic aspects of bainite formation during isothermal holding above and below the martensite start (Ms~275 °C) temperature using a low-alloy, high-silicon DIN 1.5025 steel in a range suitable for achieving ultrafine/nanostructured bainite. Dilatation measurements were conducted to study transformation behaviour and kinetics, while the microstructural features were examined using laser scanning confocal microscopy and electron backscatter diffraction (EBSD) techniques combined with har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Interestingly, the presence of a small fraction of martensite accelerates the isothermal bainite transformation. As found by Tian et al [30], Morawiec et al [32], Pashangeh et al [33], and Guo et al [34], due to the shear-like military transformation of martensite, a higher concentration of martensite increases the dislocation density and increases the internal stresses in the undercooled austenite, enhancing the driving force for the nucleation and transformation of bainite. Although they are both classified as military transformations, unlike martensite, bainitic transformation typically requires a nucleation period.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, the presence of a small fraction of martensite accelerates the isothermal bainite transformation. As found by Tian et al [30], Morawiec et al [32], Pashangeh et al [33], and Guo et al [34], due to the shear-like military transformation of martensite, a higher concentration of martensite increases the dislocation density and increases the internal stresses in the undercooled austenite, enhancing the driving force for the nucleation and transformation of bainite. Although they are both classified as military transformations, unlike martensite, bainitic transformation typically requires a nucleation period.…”
Section: Resultsmentioning
confidence: 75%
“…The diffusion of carbon and other alloying elements is restricted, resulting in a fine bainitic microstructure. Martensitic grains that form during cooling below the M S temperature act as nucleation sites and accelerate the transformation into lower bainite [30,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…7 h). Thus, the bainitic transformation time increased as the transformation temperature decreased [44]. It is well-known that the temperature of the bainite transformation affects the morphology of the structure and the degree of its refinement.…”
Section: Examination Of Phase Transformation Kinetics Based On Dilato...mentioning
confidence: 97%
“…Extensive studies and diverse processing approaches have been carried out to alter the microstructure of alloy steel and improve its impact resistance, stiffness, wear resistance, and strength [7][8][9][10][11][12]. Abbasi et al analyzed the microstructural features of three different types of medium carbon steel (namely, MnCrB-, NiCrSi-, and NiCrMoV-bearing steels) and found that the addition of small amounts of alloying elements and varying austenitic grain sizes were mainly responsible for the changes in the microstructure and mechanical properties of the steel [13].…”
Section: Introductionmentioning
confidence: 99%